Avaliação histopatológica e morfométrica intestinal dos efeitos da administração prolongada de corticosteroide em cães - Louzada, Murilo (1999)
Corticosteroids are largely used in the medical practice. However, they present side effects, that condition a risk factor for gastro-intestinal surgical procedures. The present study seeks to evaluate the histologycal changes of the mucosa and submucosa in colon of dogs submitted to the extended administration of corticosteroids.Fifteen male dogs with no defined pedigree, weighing 15 kg, randomized, being 6 dogs of the control group and 9 dogs of the experimental group, were submitted to the intramuscular application of hydrocortisone, 35 mg/kg/day for 30 days. The colonic distal segment was resected, fixed in Bouin and the courts were stained by the methods: PAS, alcian blue and HE. In the morphometric analysis, was accomplished the counting of: globet cells (GLO), absorptive cells (ABS), total cells (TOT= GLO+ABS), mitosis (MIT) and lymphocytes (LYMP) in each crypt; mast cells (MAST) in the submucosa. The histopathologycal evaluation revealed lymphocytic and plasma cells infiltrated, disorganization of the crypts, presence of pictotic cells, ulcerations in the mucosa; edema, vascular and lymphatic congestion in the submucosa. Analysis revealed: significant decrease of the number of GLO, ABS, TOT and LYMP, increase of MIT in the experimental group and non alteration of the number of MAST. It was concluded that the extended administration of corticosteroids in dogs induced significant histopathologycal and morphometric alterations in the colonic mucosa, that can be constituted important factors of surgical risk.